Analyzing Bushing Model from Optimized Numerical Model Stiffness to Improve Vehicle Noise Performances. - Kamaruzzaman, Amir Firdaus; Wan Abdul Rahman, Wan Mohd Wardi (Progress in Engineering Application and Technology, 2022)
Bushings material described as a hollow elastomer cylinder connected to the suspension system and vehicle chassis which act as strain energy potential. The extensive uses of rubber bushing (rubber isolators) are not something new where it dissipates energy between the components. The optimization of bushing stiffness is a method to reduce the vehicle noise within the components especially at the suspensions systems. In this study, the idea of the optimized bushing stiffness where its numerical model is modified were proposed initially. The optimization of the numerical model through MATLAB quadratic optimization programmed by the previous researcher were designed and analyzed to make a comparative study to the initial proposed design through a series of static and frequency (natural frequency) analysis in the Solidworks 2020. This study shows when a force of 800kgf is applied in the static analysis, the optimized rubber bushing produced better results where the stress and strain distribution on the model looked more stable. This result is supported by the natural frequency analysis where optimized rubber bushing model produced better vibration frequency and achieved higher frequency of vibrations. Bushing stiffness alterations is one of the reliable methods in terms of costing and time consumption as it is only required the modification of the rubber bushing material stiffness when compared to the other method